The SAC1 domain in synaptojanin is required for autophagosome maturation at presynaptic terminals. (22nd March 2017) - Vanhauwaert, Roeland; Kuenen, Sabine; Masius, Roy; Bademosi, Adekunle; Manetsberger, Julia; Schoovaerts, Nils; Bounti, Laura; Gontcharenko, Serguei; Swerts, Jef; Vilain, Sven; Picillo, Marina; Barone, Paolo; et al.
Abstract: Presynaptic terminals are metabolically active and accrue damage through continuous vesicle cycling. How synapses locally regulate protein homeostasis is poorly understood. We show that the presynaptic lipid phosphatase synaptojanin is required for macroautophagy, and this role is inhibited by the Parkinson's disease mutation R258Q. Synaptojanin drives synaptic endocytosis by dephosphorylating PI(4, 5)P2, but this function appears normal in Synaptojanin RQ knock‐in flies. Instead, R258Q affects the synaptojanin SAC1 domain that dephosphorylates PI(3)P and PI(3, 5)P2, two lipids found in autophagosomal membranes. Using advanced imaging, we show that Synaptojanin RQ mutants accumulate the PI(3)P/PI(3, 5)P2 ‐binding protein Atg18a on nascent synaptic autophagosomes, blocking autophagosome maturation at fly synapses and in neurites of human patient induced pluripotent stem cell‐derived neurons. Additionally, we observe neurodegeneration, including dopaminergic neuron loss, in Synaptojanin RQ flies. Thus, synaptojanin is essential for macroautophagy within presynaptic terminals, coupling protein turnover with synaptic vesicle cycling and linking presynaptic‐specific autophagy defects to Parkinson's disease. Synopsis: Parkinson's disease‐related human synaptojanin 1 (SYNJ1) or Drosophila synaptojanin (Synj) SAC1 function drives autophagosome biogenesis within synapses by dephosphorylating PI(3)P/PI(3, 5)P2, releasing WIPI2/Atg18a from immature autophagosomes, independent from Synj function in endocytosis. Parkinson's disease related synaptojanin RQ SAC1 mutation does not affect synaptic vesicle endocytosis at fly excitatory glutamatergic neurons and photoreceptors. Synaptojanin is required for autophagosome formation in presynaptic terminals, analogous to synaptic vesicle uncoating by synaptojanin. The PI(3)P/PI(3, 5)P2 ‐binding protein, WIPI2/Atg18a accumulates in Synj mutant flies and SYNJ1 R258Q patient‐derived human induced neurons. Synaptojanin regulates Atg18a mobility at autophagosomal membranes. Synaptojanin RQ knock‐in flies show neurodegeneration. Abstract : The Parkinson's disease‐associated lipid phosphatase synaptojanin promotes synaptic autophagosome formation, a function that is impaired by pathogenic mutations.